2013
DOI: 10.1128/mcb.01076-13
|View full text |Cite
|
Sign up to set email alerts
|

Tgif1 Regulates Quiescence and Self-Renewal of Hematopoietic Stem Cells

Abstract: b TG-interacting factor 1 (TGIF1) is a transcriptional repressor that can modulate retinoic acid and transforming growth factor ␤ signaling pathways. It is required for myeloid progenitor cell differentiation and survival, and mutations in the TGIF1 gene cause holoprosencephaly. Furthermore, we have previously observed that acute myelogenous leukemia (AML) patients with low TGIF1 levels had worse prognoses. Here, we explored the role of Tgif1 in murine hematopoietic stem cell (HSC) function. CFU assays showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 51 publications
1
38
1
Order By: Relevance
“…We carried out in silico analyses for Trap1a expression. As shown in Figure 5c, RNAseq data 15 showed that Trap1a was not expressed in thymocytes, whereas databases generated by others 18,19 revealed low levels of expression in BM LSK stem/progenitor cells and CLP cells (Figure 5d). Because thymocyte progenitors were identified as part of the LSK population, 21 we used PCR to validate Trap1a expression in LSK cells.…”
Section: Cell-intrinsic Function Of Trap1a In Thymocyte Developmentmentioning
confidence: 95%
See 1 more Smart Citation
“…We carried out in silico analyses for Trap1a expression. As shown in Figure 5c, RNAseq data 15 showed that Trap1a was not expressed in thymocytes, whereas databases generated by others 18,19 revealed low levels of expression in BM LSK stem/progenitor cells and CLP cells (Figure 5d). Because thymocyte progenitors were identified as part of the LSK population, 21 we used PCR to validate Trap1a expression in LSK cells.…”
Section: Cell-intrinsic Function Of Trap1a In Thymocyte Developmentmentioning
confidence: 95%
“…17 The expression values of hematopoietic stem cells, LSK and common lymphoid progenitors (CLP) were extracted from the expression result file through GEO Series accession numbers GSE50896 18 and GSE50739. 19 …”
Section: In Silico Data Analysismentioning
confidence: 99%
“…28 This is contrasted by recent in vivo experiments where BM reconstitution was inhibited by forced expression of TGIF1 and conversely promoted by its loss, perhaps suggesting a role for TGIF1 in regulating hematopoietic stem cell (HSC) biology. 29 Finally, unpublished observations cited in various reports suggest that TGIF1 expression is a favorable prognostic factor in AML patients, raising the possibility that TGIF1 may have a role in leukemogenesis. [28][29][30][31] Here we have focused on the function of TGIF1 in MLLrearranged AML and demonstrate that it interferes with an MEIS1-dependent transcriptional network required for AML maintenance by directly competing with MEIS1 for binding to common regions within the chromatin.…”
Section: Introductionmentioning
confidence: 96%
“…TGIF family includes two members, TGIF1 and TGIF2 [16]. Previous studies showed the pivotal functions of TGIF in holoprosencephaly, adipocyte differentiation, hematopoietic stem cell, and vascularization [17][18][19][20]. Also, the functions of TGIF in cancer, including leukemia [21], gastric cancer [22], and ovarian cancer [23], were reported.…”
Section: Introductionmentioning
confidence: 98%